Assessment of Spatial Variation of Water Quality of Tunggak River Adjacent to Gebeng Industrial Estate, Malaysia - M. A., Hossain; Islam, Mir Sujaul; Nasly, Mohamed Ali; Zularisam, A. W.; Edriyana, Abd Aziz (Bangladesh Environment Network Japan, 2012)
Anthropogenic impact on the Tunggak River is as a result of rapid industrialization in the study area. The study was conducted with the objective to explore the spatial variation of the water quality of the river due to anthropogenic activities. Water samples were collected monthly from selected sites and analyzed applying APHA & HACH standard methods. Trace elements were determined using Inductively Coupled Plasma Mass Spectrophotometer (ICP-MS). SPSS statistical software was used for data analysis. The study revealed that point sources especially industrial wastes contributing the major pollutants. Less amount of dissolved oxygen (DO) and higher concentration of chemical oxygen demand (COD) & ammoniacal nitrogen and trace elements made the water unusable. Based on Department of Environment-Water Quality Index (DOE-WQI) Malaysia, maximum stations except lower and uppermost were categorized as class IV (highly polluted). Pollution was higher in the middle stations due to addition of most of the industrial effluents to those sites.